Methyl gallate, gallic acid-derived compound, inhibit cell proliferation through increasing ROS production and apoptosis in hepatocellular carcinoma cells. - Chien-Yu Huang; Yu-Jia Chang; Po-Li Wei; Chin-Sheng Hung; Weu Wang (PLoS ONE)
Hepatocellular carcinoma (HCC) is a global health problem. Currently, there is no effective therapeutic strategy for HCC. Methyl gallate (MG), from plant-derived phenolic gallic acid, has exhibited antitumor efficacy. However, the effect of MG on HCC is unclear. In vitro growth activity was detected by a sulforhodamine assay. A zebrafish xenotransplantation was applied to evaluate the inhibitory effect of MG. Reactive oxygen species (ROS) production, autophagy, and lysosome formation were detected by specific dyes. Finally, apoptosis was examined using annexin V-FITC/PI staining and western blot was performed to determine the molecular mechanism. It was demonstrated that MG treatment inhibited the proliferation of Hep3B, Mahlavu, and HepJ5 cells. Xenotransplantation also showed that MG inhibited the growth of Hep3B and HepJ5 cells. MG treatment increased cellular levels of superoxide and oxidative stress. Increases in autophagy and lysosome formation were found after MG treatment. The western blot analysis showed that MG activated cleavage of caspase-3 and poly (SDP ribose) polymerase (PARP), modulated levels of the Bcl2, Bax, and Bad ligands, and induced apoptosis. MG induced autophagy with notable activation of beclin-1, autophagy related 5+12 (ATG5+12), and conversion of light chain 3-I (LC3-I) to II. Our study showed that MG exposure inhibited HCC proliferation both in vitro and in vivo. And blocking autophagy enhanced MG-induced cytotoxicity in HCC cells. These findings suggested MG might serve as a powerful therapeutic supplement for human HCC patients.